An introduction to thermodynamic cycle simulations for internal combustion engines - Caton, J. A. (John Wiley & Sons Inc., 2016)
This book provides an introduction to basic thermodynamic engine cycle simulations, and provides a substantial set of results. Key features includes comprehensive and detailed documentation of the mathematical foundations and solutions required for thermodynamic engine cycle simulations.